2006
DOI: 10.1126/science.1130563
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Coronin 1 in T Lymphocyte Trafficking and Cellular Homeostasis

Abstract: The evolutionarily conserved actin-related protein (Arp2/3) complex is a key component of actin filament networks that is dynamically regulated by nucleation-promoting and inhibitory factors. Although much is known about actin assembly, the physiologic functions of inhibitory proteins are unclear. We generated coronin 1-/- mice and found that coronin 1 exerted an inhibitory effect on cellular steady-state F-actin formation via an Arp2/3-dependent mechanism. Whereas coronin 1 was required for chemokine-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
281
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(311 citation statements)
references
References 25 publications
21
281
3
Order By: Relevance
“…In this model, Coronin 1A localizes to the plasma membrane in resting cells together with Cofilin where they bind to PI(4,5)P 2 and are therefore inactivated. This model is also supported by a recent study suggesting that a constitutive targeting of Coronin 1B to the plasma membrane strongly enhances its phosphorylation (14), which negatively regulates Coronin activity by reducing its affinity for the Arp2/3 complex (12,30). Upon growth factor stimulation, activated PLC hydrolyzes PI(4,5)P 2 , thus inducing Coronin 1A and Cofilin translocations from the plasma membrane to the F-actin compartment of lamellipodia, where these molecules will be dephosphorylated by Slingshot.…”
Section: Discussionsupporting
confidence: 68%
“…In this model, Coronin 1A localizes to the plasma membrane in resting cells together with Cofilin where they bind to PI(4,5)P 2 and are therefore inactivated. This model is also supported by a recent study suggesting that a constitutive targeting of Coronin 1B to the plasma membrane strongly enhances its phosphorylation (14), which negatively regulates Coronin activity by reducing its affinity for the Arp2/3 complex (12,30). Upon growth factor stimulation, activated PLC hydrolyzes PI(4,5)P 2 , thus inducing Coronin 1A and Cofilin translocations from the plasma membrane to the F-actin compartment of lamellipodia, where these molecules will be dephosphorylated by Slingshot.…”
Section: Discussionsupporting
confidence: 68%
“…An earlier study of coronin 1A knock-out mice reported that coronin 1A has an Arp2/3-5-dependent inhibitory effect on F-actin formation and concluded that coronin 1A is indispensable for TCR signaling (27,29). In the present study, overexpression of coronin 1A restored the proliferative response.…”
Section: Discussionsupporting
confidence: 66%
“…The Arp2/3 (actin-related protein 2/3) complex has been reported to be essential for TCR-mediated cytoskeletal reorganization (23,24), and Arp2/3 complex-mediated actin nucleation is required for the formation of an F-actin-rich lamellipod (22,25,26). Coronin 1A is preferentially expressed in hematopoietic cells and co-localizes with F-actin-rich membranes in activated T cells (27). Coronin 1A has been shown to bind the Arp2/3 complex and inhibit F-actin nucleation by freezing the Arp2/3 complex in its inactive conformation (28).…”
mentioning
confidence: 99%
“…More recently, it was reported that the p57/coronin-1 gene was responsible for human and mouse severe combined immunodeficiency (22,23). In mice deficient in the p57/coronin-1 gene, differentiation and chemokine-mediated trafficking of T cells were severely impaired (22,24,25). It was further demonstrated that the developments of experimental autoimmune encephalomyelitis (26,27) and lupus-like autoimmune disease (28) were suppressed in mice with genetic defects of p57/coronin-1.…”
mentioning
confidence: 82%
“…8A). Indeed, it has been suggested that p57/coronin-1 physically interacts with the Arp 2/3 complex and that the interaction is weakened by the mutation at Ser-2 of p57/coronin-1 in lymphocytes (24,32); i.e. the wild-type and S2A mutant (in which Ser-2 was replaced with Ala) of p57/coronin-1 bound to the Arp 2/3 complex, whereas the phosphorylation mimic S2D (in which Ser-2 was replaced with Asp) exhibited decreased binding activity, suggesting the possible involvement of Ser-2 phosphorylation in the interaction between p57/coronin-1 and the Arp 2/3 complex.…”
Section: Discussionmentioning
confidence: 99%